The role of the organization’s strategic orientation in achieving social responsibility through the interactive role of strategic leadership (A survey study in Dhi Qar Oil Company) - Hayder, Shamkhi; Abd El Sattar, A.M. Dr Nada (The Gulf Economist, 2025)
This study aims to demonstrate the effectiveness of risk management in achieving total quality. Its scientific importance originates from two perspectives. First, risk management and total quality management constitute two basic pillars organizations rely on to achieve their goals and enhance their position in a highly competitive market. The second perspective comes from the importance of the community in which the study was conducted (Basra Oil Company) and its economic importance at local and global levels. The study began with a series of surveys and interviews conducted by the researcher with several officials in the community in which the study was conducted to develop a vision to explain the problem in preparation for the study in its theoretical and practical aspects. This paper is divided into four chapters. In the first chapter, the scientific methodology for the research is prepared, and some studies are reviewed, including theses, dissertations, and scientific research. It was conducted in the fields of quality and risk management, which benefitted greatly from a theoretical perspective. This was the share of the second chapter, which dealt with the most important concepts, principles, and scientific foundations that could contribute to enabling organizations to manage all risks that stand in the way of achieving their goals and achieving comprehensive quality. As for the practical aspect, it was the share of the third chapter, where the validity and consistency of the data were verified, and descriptive analyses were conducted, ending with testing the hypotheses. Several software programs prepared for this purpose were used, including SPSS V.26, JASP V.19, AMOS V.24, and Excel. Two main hypotheses were developed, each of which was divided into four sub-hypotheses. An exploratory approach is used in this study. Considering this approach, a sample was intentionally taken from the population to investigate the relationships between the variables. The results of the analyses revealed significant correlations between the variables under study, confirming the initial assumptions made in the hypotheses. Finally, employees working in bodies and departments obtained ISO certificates by distributing 400 questionnaires. The number of returned forms was 346, of which 12 were invalid forms and 334 were valid forms for which data were processed. The fourth chapter is the fruit-picking stage of this study, as its purpose was achieved, which is to prove the effective role played by risk management in achieving comprehensive quality, in addition to presenting some conclusions that resulted from the theoretical side and several proposals, which the researcher believes contribute to achieving institutional goals and adding cognitive value to existing knowledge